Investigating the Relationships between Problem-Solving Ability, Resilience and Academic Burnout in Virtual Medical Education Students Using Structural Equation Modeling - Z. Khoshgoftar; F. Karamali; M.Z. Nasrabadi; M.H. Nejad (Moscow State University of Psychology and Education, 2023)
the purpose of the present study is to investigate the relationship between academic resilience and academic burnout through the mediation of problem-solving ability.Research questionnaires (demographics, academic burnout, academic resilience and problem-solving ability) were sent online through Press Online software in 2021 for a sample size of 260 students of virtual medical education. Descriptive statistics, Pearson correlation and Structural equation modeling were used to examine the characteristics of the participants, correlation between main variable and test the study hypothesis. Based on the results the model fit indices CFI (comparative fit index), NFI (normed fit index), TLI (Tuckere Lewis index), X2/DF (the ratio of X2 to degrees of freedom) and RMSEA (Root mean of square error approximation) were appropriate. it was found that the academic burnout with problem solving skill (β = -0.77), academic resilience (β = 0.26) and problem-solving skill with academic Resilience (β = 0.96) has a statistically significant relationship. Also, it was found that most of the relationship between academic burnout and academic resilience is indirect and through the mediator variable of problem-solving skills (-0.871).The results of this research determined that there is a certain group of students suffering from burnout and weak problem-solving skills, who are at risk. Screen such students and provide them with short courses aimed at developing adaptive coping skills, such as problem solving, which can prevent their academic burnout.